Sterically hindered cyclic diynes: syntheses and structures - Schaefer, Carsten; Gleiter, Rolf; Rominger, Frank (European journal of organic chemistry, 2003)
The synthesis of three 14-membered ring systems 8a−8c with the 1,3,8,10-tetraoxa-2,9-disilacyclotetradeca-5,12-diyne skeleton is described. In all three ring systems the α-positions are substituted with gem-dimethyl and/or gem-diphenyl groups. Structural investigations on 8a and 8c reveal a chair like conformation of the central ring with parallel alkyne units. For 8b the voluminous phenyl groups cause a twist-chair and a twist-boat conformation. Columnar structures were encountered for 8a in the solid state. Reactions with octacarbonyldicobalt yield for 8a mono- and biscomplexation (12, 13). For 8b only the mono complexation product 14 was isolated. For 8c the bis(hexacarbonyldicobalt) complex 15 was obtained. X-ray investigations revealed columnar structures in the solid state for 12, 13, and 15. (© Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2003)